A holistic framework for designing for structural robustness in tall timber buildings. (15th January 2021) - Voulpiotis, Konstantinos; Köhler, Jochen; Jockwer, Robert; Frangi, Andrea
Highlight: Review of structural robustness and its relation to tall timber building design and construction; Suggestion of a method to analyse structures based on a multi-level scale approach; Reconsideration of structural robustness design via the scale approach; Recommendation of a conceptual design for a tall timber building based on this method; Suggestion of a quantitative framework to design robust buildings; Presentation of a case study example of the application of the proposed framework. Abstract: With the ever-increasing popularity of engineered wood products, larger and more complex structures made of timber have been built, such as new tall timber buildings of unprecedented height. Designing for structural robustness in tall timber buildings is still not well understood due the complex properties of timber and the difficulty in testing large assemblies, making the prediction of tall timber building behaviour under damage very difficult. This paper discusses briefly the existing state-of-the-art and suggests the next step in considering robustness holistically. Qualitatively, this is done by introducing the concept of scale, that is to consider robustness at multiple levels within a structure: in the whole structure, compartments, components, connections, connectors, and material. Additionally, considering both local and global exposures is key in coming up with a sound conceptual design. Quantitatively, the method to calculate the robustness index in a building is presented. A novel framework to quantify robustness and find the optimal structural solution is presented, based on the calculation of the scenario probability-weighted average robustness indices of various design options of a building. A case study example is also presented in the end.